Angiogenesis in the Placenta: The Role of Reactive Oxygen Species Signaling. (29th January 2015) - Pereira, Robyn D.; De Long, Nicole E.; Wang, Ruijun C.; Yazdi, Fereshteh T.; Holloway, Alison C.; Raha, Sandeep
Abstract : Proper placental development and function are central to the health of both the mother and the fetus during pregnancy. A critical component of healthy placental function is the proper development of its vascular network. Poor vascularization of the placenta can lead to fetal growth restriction, preeclampsia, and in some cases fetal death. Therefore, understanding the mechanisms by which uterine stressors influence the development of the placental vasculature and contribute to placental dysfunction is of central importance to ensuring a healthy pregnancy. In this review we discuss how oxidative stress observed in maternal smoking, maternal obesity, and preeclampsia has been associated with aberrant angiogenesis and placental dysfunction resulting in adverse pregnancy outcomes. We also highlight that oxidative stress can influence the expression of a number of transcription factors important in mediating angiogenesis. Therefore, understanding how oxidative stress affects redox-sensitive transcription factors within the placenta may elucidate potential therapeutic targets for correcting abnormal placental angiogenesis and function.